Heme-Iron OptiFer® in the Treatment of Iron Deficiency Anemia During Pregnancy - Ibrahim A. Abdelazim; Mohannad AbuFaza; Soud M. Al-Ajmi; Osama O. Amer; Svetlana Shikanova; Bakyt Karimova (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: This study designed to compare the efficacy, and tolerability of heme-iron OptiFer® to ferrous fumarate in the treatment of iron deficiency anemia during pregnancy.